Persepsi Mahasiswa Terhadap Kualitas Layanan Bimbingan Skripsi Di Perguruan Tinggi Kota Makassar - Sri Rahayu Fadliyah; Faridah; Sumarlin Mus (LP2M IAIN Sultan Amai Gorontalo, 2025)
The improvement of thesis supervision service quality in higher education is a crucial aspect in supporting the smooth progression of studies and the academic success of students. This study aims to explore students’ perceptions of the quality of thesis supervision services at the Faculty of Education, , focusing on five SERVQUAL dimensions: Tangibles, Reliability, Responsiveness , Assurance, and Empathy. A descriptive quantitative approach was employed using a survey method. The instrument was a closed-ended questionnaire based on a 10-point semantic differential scale, consisting of 34 statement items, and was distributed online to 327 students. The data were analyzed using descriptive statistics through frequency and percentage distribution. The findings indicate that, in general, students’ perceptions fall into the “very good” category across most service dimensions. The Tangibles dimension was rated as very good, reflecting the availability of adequate supervision rooms, comprehensive thesis guidelines, and the effective use of digital communication media. The Reliability dimension also received a very good evaluation, indicating the consistency and accuracy of supervisors in performing their supervisory duties. The Responsiveness dimension was rated as good, suggesting that supervisors were reasonably responsive in providing feedback and allocating time for students. The Assurance dimension received the highest score within the very good category, demonstrating students’ strong trust in their supervisors’ competence, integrity, and professionalism. Meanwhile, the Empathy dimension was also rated as very good, reflecting the care, concern, and ability of supervisors to understand students’ individual conditions. Overall, the results indicate that the thesis supervision services have met students’ expectations, although some aspects, particularly within the Responsiveness dimension, still require improvement.